Hospital Pharmacy Compounding against COVID-19 pandemic - José María Alonso-Herreros; Silvia Berisa-Prado; Carme Cañete-Ramírez; María del Pilar Flox-Benítez; Margarita Ladrón de Guevara-García; Carmen López-Cabezas; Ana María Martín de Rosales-Cabrera; Beatriz Ramos-Martínez (Elsevier, 2020)
As in other areas of the health system, COVID-19 has had a dramatic impact on hospital compounding. This area has faced numerous challenges, including the shortage of frequent-use products (hydroalcoholic solutions, lopinavir/ritonavir suspension), the use of new preparations for SARS-CoV-2 (tocilizumab, remdesivir), or requests from overwhelmed wards unable to assume the safe preparation of a high volume of medications (intravenous solutions). The demand for all types of preparations (topic and oral medications, intravenous solutions) has increased dramatically. This increase has highlighted the shortage of resources allocated to this area, which has made it difficult to meet the high demand for preparations. In addition, the pandemic has revealed the scarcity of research on such basic aspects as agent stability and drug compatibility. One of the most relevant conclusions drawn from the COVID-19 pandemic is that the basic areas of hospital pharmacy, along with other, must be maintained and reinforced, as these are the areas that make us essential.